TECHNOLOGIСAL MODES OF LASER PROCESSING AND THEIR INFLUENCE ON PHYSICAL AND MECHANICAL PROPERTIES OF Fe–Cr–B–Si COATINGS - O. V. Diachenko (Наука и техника)
The paper investigates an influence of laser processing modes pertaining to gas-thermal coatings of iron- based powders after melting with modifying coatings on their micro-hardness, microstructure and porosity. Conditions for obtaining of coatings with the most uniform distribution of alloying substances have been revealed in the paper. The paper considers characteristics of porosity changes in Fe-Cr-B-Si coatings due to speed of movement, diameter and temperature of a laser beam spot.